Intrastate travel experiences of international students and their perceptions of Western Australia as a tourist destination - Shanka, Tekle; Ali-Knight, Jane; Pope, Jeff (Henry Stewart Publications, 2002)
This paper presents initial findings from a study examining the impact on Western Australian (WA) tourism of the growing number of international students in the state. Focusing on one university with the largest number of international students (3,946 onshore students in 2000) the study examines the intrastate travel behaviour and student perception of WA as a tourist destination. Both undergraduate and postgraduate international students were sent a self-administered questionnaire and this paper presents the findings of travel experiences of these students while doing their studies in the state. The results indicate the importance of the international student market for regional tourism and confirm its contribution to the domestic tourism market.